ANALISIS PERMINTAAN TEPUNG AREN AGUNG JAYA OLEH INDUSTRI DAN RUMAH TANGGA DI KOTA BANDAR LAMPUNG - Asrifa, Ajeng Kurnia; Lestari, Dyah Aring Hepiana; Sayekti, Wuryaningsih Dwi (Lampung University, 2025)
This study aims to determine the purchasing pattern of Agung Jaya palm flour by home industry and the demand for Agung Jaya palm flour by households in Bandar Lampung. This research was conducted in Bandar Lampung, from September 2023 - October 2023. The samples used in this study were all home industries that bought Agung Jaya palm flour and 50 households that had bought Agung Jaya palm flour. Household samples were selected by accidental sampling method. The research data were analyzed by descriptive analysis and multiple linear regression. The results showed that the home industry bought Agung Jaya palm flour 2 - 4 times/month with an amount of 5 kg - 80 kg/purchase, so the average purchase was 118 kg/industry/month. The palm flour sold to the home industry is a type of bulk palm flour with a price of Rp10,000/kg. Industries that made purchases consisted of the cendol dawet processing industry, frozen food, meatballs, and chicken noodles, as well as wet cakes. In the analysis of household demand, it is known that the price of rice, number of household members, knowledge of diversification, and taste affected the demand for Agung Jaya palm flour at the household level in Bandar Lampung.